Using Communicative Language Teaching to Improve Speaking Skills of the Tenth-Grade Students at Senior High School - Suci Salsabila; Nadrun; Desrin lebagi; Mochtar Marhum (Institut Agama Islam Negeri Palopo, 2025)
This study aims to determine the effectiveness of using communicative language teaching to improve the speaking skills of the tenth-grade students at SMA Negeri 1 Ampibabo. This study used a quasi-experimental research design with two classes designated as a control class and the experimental class. The sample in this research has tenth-grade students. In collecting the data, the researchers used pretests and posttests. The collected data were analyzed using SPSS version 23. The result shows that the mean score of posttests of the students in the experimental class (62.02) was higher than the mean score in the control class (55.16). Based on the results of the independent sample t-test, the sig (2-tailed) value (0.000) was less than 0.050. This study shows that the alternative hypothesis is accepted. While means using communicative language teaching effectively to improve the speaking skills of the tenth-grade students at SMA Negeri 1 Ampibabo.